Enhancing the Representativeness of the Ethiopian Electoral System: A Case for a Mixed Member Proportional (MMP) Electoral System - Beyene, Temesgen Sisay (Bahir Dar University Journal of Law, 2022)
Electoral systems can be understood as a means by which popular votes can be converted into parliamentary seats on the basis of a scheme designed for this purpose by respective states. As specific contexts obviously vary, states are free to design an electoral system that best fits their particular realities. Designing an appropriate electoral system, however, essentially involves balancing its representativeness and accountability objectives. The purpose of this article is to investigate the salient features of the dominant electoral systems which are being practiced in major democracies of the world and identify a system that appropriately fits the Ethiopian context. Based on critical analysis of the majoritarian and proportional electoral systems and appraisal of the existing Ethiopia’s electoral system, it is argued that a Mixed Member Proportion (MMP) electoral system, which is an aspect of a mixed electoral system, best fits the Ethiopian situation as it can ensure representativeness and accountability together.